PEMBUATAN SURFAKTAN DARI MINYAK KELAPA MURNI (VCO) MELALUI PROSES AMIDASI DENGAN KATALIS NaOH - Astri Probowati; Paradigma Carlo Giovanni; Diyono Ikhsan (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
The used of coconut oil of surfactant has several advantages, among others, are renewable resources, cleaner, and more pure than the used of petrochemical-based raw materials. Thus the necessary research to obtain a surfactant that has those criteria. One of the surfactant that meet both criteria is diethanolamide surfactant. The materials used for the manufacture of methyl ester is VCO and methanol with a catalyst H2SO4 while the materials used for the amidation are methyl ester from VCO, and diethanolamine with catalyst NaOH. The tools used in this research are tree neck flask, cooling loop, magnetic stirrer, waterbath, stative and clamps. From the research results obtained at high conversion, namely the mole ratio of methyl ester : diethanolamine 1:2 that is equal to 71,4% and percent weigth of catalyst is 1% with mole ratio 1:1.25 is 70,8%. From this research can be concluded the greater the mole ratio of the reactant and percent weight of the catalyst then the greater the resulting conversion.